Pemilihan Masker Standar Pencegahan Penularan Covid-19 di Kelurahan Talang Banjar - Iin Indrawati; Faridah Faridah (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
In Indonesia, currently they are still fighting the Corona / Covid 19 Virus, as well as in other countries. The number of cases affected by patients continues to grow. In several reports reported recovery, but not a few who died. Information dissemination aims to change people's attitudes, beliefs and behavior through providing information and raising awareness that a problem that arises can be overcome, especially in terms of preventing the transmission of Covid 19 through the selection and use of good and correct masks.Providing correct knowledge to the public can be done in various ways, one of which is by directly socializing the knowledge that will be given. This community service activity is carried out by extension methods, distributing information brochures, distributing masks and directly teaching the community how to use masks and choosing the right and good masks.After health education was carried out, the community understood and wanted to choose masks and use masks correctly. The public also understands the importance of taking preventive measures so as not to be infected or exposed to the Covid 19 virus.Health education activities should be carried out routinely by health workers in order to improve public health by changing people's life habits to be clean and healthy ones